Associations amongst form of cocaine used (powder vs crack vs both) and HIV-related outcomes. (December 2021) - Liu, Yiyang; Richards, Veronica L.; Gebru, Nioud Mulugeta; Spencer, Emma C.; Cook, Robert L.
Highlights: Among PWH, cocaine use vs no-use was associated with worse HIV treatment outcomes. Powder cocaine only users were more likely to be younger, Hispanic, and employed. Users of powder + crack cocaine had lower viral suppression than users of either alone. Harm reduction efforts addressing substance use should be a key component of HIV care. Abstract: Introduction: Cocaine (including powder and crack) use is common among people with HIV (PWH). We identified socio-demographic and behavioral factors associated with cocaine use (overall and various forms) among PWH; we also examined differences in HIV treatment outcomes across cocaine exposure groups. Methods: The study sample (N = 1166) was derived from two cohorts of PWH in Florida between 2014 and 2020. Baseline data were linked to the Enhanced HIV/AIDS Reporting System (eHARS) which tracks HIV viral load. Socio-demographics and polysubstance use were compared by cocaine use and the three cocaine use groups (powder only n = 101, crack only n = 91, or both n = 65). The association between the three cocaine use groups, ART adherence, and HIV viral suppression (<200 copies/mL) in the following year was assessed by multivariate logistic regression. Results: People who used cocaine had lower HIV treatment adherence and viral suppression than those who did not use. People who used powder cocaine only were more likely to be younger, Hispanic/Latinx, and employed than those who used crack only or both. Compared to people who used both powder and crack cocaine, those who used one form of cocaine had 3 + odds of having durable viral suppression in the following year. Conclusion: The dual use of both powder and crack cocaine was associated with significantly worse HIV outcomes compared to use of only one form of cocaine. Screening for powder and crack cocaine use and timely intervention are needed to improve HIV treatment outcomes among this high-risk population.